Pengaruh book tax differences, aliran kas, tingkat hutang terhadap perubahan laba (studi empiris pada perusahaan real estate and property yang terdaftar di bei 2010-2012) - Wira Amelia; Zirman '; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study was conducted to examine empirically the effect of book taxdifferences, cash flow, and level debt to income changes.The population used in this study are real estate companies and propertylisted in Indonesia Stock Exchange during the period 2010-2012, with a total population of 53 companies. This study used a purposive sampling method, with a total sample of 31 companies. The method of analysis used in this study is the method of linear regression analysis with SPSS version 22.The results showed that the effect of permanent differences to changes inearnings with significance 0.001 <0.05. Temporary distinction has no effect on the change in earnings with a significance value 0.246 <0.05 level. Cash flow effect on earnings changes with the value of 0.017> 0.05 level. And debt levels do not influence the change in earnings with significant value 0.519 <0.05. R-square value is equal to 0.137 which means that 13.7% of the independent variable in this study is able to influence the dependent variable, while the remaining 86.3% is explained by other variables not included in the study.Keywords: permanent differences, temporary differences, cash flows, debt levels and earnings changes